2019
DOI: 10.1016/j.jmst.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Negative permittivity derived from inductive characteristic in the percolating Cu/EP metacomposites

Abstract: Recently, increasing attention has been concentrated on negative permittivity with the development of the emerging metamaterials composed of periodic array structures. However, taking facile preparation into consideration, it is important to achieve negative permittivity behavior based on materials' intrinsic properties rather than their artificially periodic structures. In this paper, we proposed to fabricate the percolating copper/epoxy resin (Cu/EP) composites by a polymerization method to realize the negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 52 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…With the increase of graphene content, the connectivity of the graphene sheets increases, so it is inevitable to generate the leakage current especially when the graphene content is in the vicinity of percolation threshold. As is well known, the dielectric constant is related to the polarization of dipoles in materials 55. Absolutely, the leakage current is detrimental to the polarization of dipoles, so the permittivity in the GR/PVA composites with 18 wt% graphene got lessened.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…With the increase of graphene content, the connectivity of the graphene sheets increases, so it is inevitable to generate the leakage current especially when the graphene content is in the vicinity of percolation threshold. As is well known, the dielectric constant is related to the polarization of dipoles in materials 55. Absolutely, the leakage current is detrimental to the polarization of dipoles, so the permittivity in the GR/PVA composites with 18 wt% graphene got lessened.…”
Section: Resultsmentioning
confidence: 97%
“…According to the free electron gas theory, the positive and negative charges can separate from each other and generate a slight displacement; under the action of an alternating electric field, the electrons can give rise to a collective harmonic oscillation, which called plasma oscillation 55. It is indicated that the permittivity of conductive materials commonly presented negative values, when the test frequency is below the plasma oscillation frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbing mechanism for Ag@MWCNT hybrids is demonstrated in Figure . The possible reason for the enhanced absorbing performance is as follows: (1) MWCNTs belong to the dielectric loss absorbing material, while conductive Ag had resistance loss characteristics . The combination of MWCNTs with Ag microspheres would generate synergy effect to collectively attenuate the energy of EM waves.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Electron migration and electronic hopping between the Ag−Ag particles, MWCNTs−Ag particles, and MWCNTs−MWCNTs would be generated, which was helpful to transform EM energy into heat energy or other forms. Based on the above analysis, the deposited conductive Ag on the PS microspheres could increase the interfacial polarization and resistance loss, 42 which was quite meaningful to improve the absorption properties.…”
Section: Analysis Of Dielectricmentioning
confidence: 87%
See 1 more Smart Citation